Pengembangan Paket Bimbingan Konseling Covid-19 Berbasis Ajaran Islam dan Dakwah serta Pengaruhnya dalam Mencegah Penyebaran Covid di Kota Makassar - Abdul Hadis; Nurhayati B; Usman Usman (Seminar Nasional LP2M UNM, 2022)
Abstrak. The fact shown that distributed Covid-19 infection to the peoples of Makassar City not yet final. This caused application, understanding, and knowledge of peoples is low about cleaning and dangerous of Covid-19. Therefore, the goal of this research is for product of counseling and guidance Covid-19 based dakwah dan Islam. From this development research, opportunited fist year birth product Covid-19 Counseling and Guidance dan at second year of this research is experimentation this product fot konow effect to preventive distribution infection of Covid-19. This research design is development research with adoption of Dick and Carey model pasca adaptation by researchers team Kata Kunci: Counseling and guidance, Covid-19, Islam and Dakwah